Measuring the concentration of 222Rn and 226Ra in a group of oil sludge samples from some Maysan oil fields using nuclear track - Murtadha Mohammed Al-Zahiwat ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Environmental monitoring of external and internal radon is very important for public health. To assess the possibility of respiratory cancer, the study dealt with collecting (81) samples of sludge produced as waste from the oil industry from oil fields in Maysan Governorate, southern Iraq. The aim of the study was to determine the concentrations of radon gas (222Rn) and the concentration of radium, and the effective dose resulting from the release of radon gas on the body and lung tissues was calculated. CR-39 trace detector technology was used to accomplish this work. It was found that the Fakka fields contain a high concentration of radium, the main cause of radon, while it was lower in the Bazargan fields. In all samples, the concentration of radium (226Rn) and the radon gas released from it was much higher than the permissible dose level recommended by the International Commission on Radiological Protection.